'Re-souling daily life' – towards a restored spirituality of the Sabbath as a cure for 'societal madness'. Issue 3 (3rd July 2018) - Mudge, Peter J. P.
Abstract: In a world of busyness bordering on 'madness' (referring here to fanatical and foolish behaviour and not to serious mental illness), technological dominance, and constant, unreflective activity, a renewed spirituality of the Sabbath is essential for a flourishing, fulfilling and spiritual life, for both children and adults. The topics of silence, leisure and to a smaller extent Sabbath, have been treated in a limited number of articles within this journal – hence the relevance and timeliness of this contribution. This article begins with working descriptions of spirituality. It then proceeds to an examination of the nature of societal 'madness' as insanity. The article also explores Jewish, Christian and Benedictine perspectives on the topic, and points throughout to a range of values and disciplines that might assist the reclamation of a sustained Sabbath consciousness and the 're-souling' (renewing, re-Spiriting) of everyday life, such as 'mindful walking'.